NUTRITIONAL AND CAROTENOID CHARACTERIZATION OF YELLOW PUMPKIN (Cucurbita moschata) POWDER FOR POTENTIAL USE IN ORNAMENTAL FISH FEED - Islamy, R. Adharyan; Faqih, Abd Rahem; Putra, Arya Darmawan Kurniadi; Ramadhani, Auryn Novia; Czech, Michael (Journal of Aquatropica Asia, 2025)
Yellow pumpkin (Cucurbita moschata) is a natural plant source rich in carotenoids, particularly β-carotene, with promising potential as a functional ingredient in ornamental fish diets. This study aimed to evaluate the nutritional composition and carotenoid profile of yellow pumpkin powder as a preliminary step toward its application in enhancing fish coloration. Proximate analysis revealed high carbohydrate content (61.25%), crude fiber (10.48%), and moderate protein levels (13.26%). Furthermore, the β-carotene content reached 102.4 mg/kg, highlighting its value as a natural pigment source. Essential minerals such as potassium, calcium, and magnesium were also present in considerable amounts. These findings suggest that yellow pumpkin powder is a nutritious, sustainable, and pigment-rich feed ingredient suitable for use in ornamental aquaculture.